Pengembangan Strategi Komunikasi Simbolik untuk Branding Pengamen - Misnan, Misnan; Bachtiar, Alfan; Barizki, Rezzi Nanda; Desilawati, Nur; Putri, Erita Riski (ABDI KAMI: Jurnal Pengabdian Kepada Masyarakat, 2025)
Buskers in Lenteng Agung, South Jakarta, often face negative stigma from society, which perceives their activities as disturbing. The lack of effective communication strategies makes it difficult for them to build a more positive and professional image. To address this issue, this community engagement program aims to develop symbolic communication strategies to strengthen the branding of street musicians. The method employed in this program includes an initial survey to identify the musicians’ needs, followed by a two-day workshop covering theoretical and practical training in symbolic communication, visual identity development, and social media promotion strategies. After the workshop, participants receive individual consultation sessions to design a suitable branding strategy, which they implement daily. Monitoring and evaluation are conducted over one month to assess the effectiveness of the training. The program results indicate a significant improvement in the musicians' understanding and skills related to symbolic communication strategies and branding. Post-test results show a 90% increase in understanding of symbolic communication concepts, a 70% improvement in social media utilization for promotion, and an 80% enhancement in visual identity application. Additionally, participants’ confidence in building a more professional image increased by 80%. These findings suggest that the training successfully enhanced the symbolic communication skills of street musicians, transforming their negative stigma from being perceived as "disturbances" to being recognized as "entertainers."